2017
DOI: 10.1186/s12245-017-0149-4
|View full text |Cite
|
Sign up to set email alerts
|

Team communication patterns in emergency resuscitation: a mixed methods qualitative analysis

Abstract: BackgroundIn order to enhance patient safety during resuscitation of critically ill patients, we need to optimize team communication and enhance team situational awareness but little is known about resuscitation team communication patterns. The objective of this study is to understand how teams communicate during resuscitation; specifically to assess for a shared mental model (organized understanding of a team’s relationships) and information needs.MethodsWe triangulated 3 methods to evaluate resuscitation tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
(5 reference statements)
2
20
0
Order By: Relevance
“…Other studies have found that decision support systems that support the whole team have the potential to enhance team performance, team communication and situational awareness. (28,29). Our participants, whilst accepting the merit of the second screen as a means of improving organisation and communication, some participants felt that the introduction of information resulted in loss of control and recommended that future devices should provide only the information that was required at that particular point in time.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that decision support systems that support the whole team have the potential to enhance team performance, team communication and situational awareness. (28,29). Our participants, whilst accepting the merit of the second screen as a means of improving organisation and communication, some participants felt that the introduction of information resulted in loss of control and recommended that future devices should provide only the information that was required at that particular point in time.…”
Section: Discussionmentioning
confidence: 99%
“…Unfamiliar staff, infrequent exposure to anaesthetic or perioperative emergencies, managing older or nonstandard equipment and isolation from colleagues may add to the cognitive load of the anaesthesiologist. Cognitive aids may help reduce this load, alleviate stress and provide a shared mental model for those staff members involved [49]. Hospital working conditions during pandemics such as SARS-CoV-2 are particularly challenging and it is exactly this environment in which cognitive aids may contribute to improved outcome for patients and HCWs.…”
Section: Cognitive Aidsmentioning
confidence: 99%
“…The roles of each team member in the healthcare environment should be understood in order to provide rapid, life-saving and effective delivery of health services (Calder et al, 2017). Rajah et al (2017) also suggested standardized health literacy communication techniques guidelines for improving good healthcare delivery.…”
Section: Communication Issues In Healthcare Environmentmentioning
confidence: 99%